Self-Reported Academic Performance and Lifestyle Habits of School Children in Japan - Kohyama, Jun (International Journal of Child Health and Nutrition, 2017)
Background and Objective: The purpose of this study was to determine the lifestyle habits significantly associated with self-reported academic performance (AP) in children in grades 5 to 12 in Japan. Methods: A total of 2,114 completed questionnaires were analyzed. Factors examined included habits related to sleeping, eating, defecation, physical activity, and screen time, in addition to body mass index (BMI). Social jet lag (SJL) was calculated from sleeping factors and categorized into five groups according to its value: minus 1 or less (SJL 1), more than minus 1 and 0 or less (SJL 2), more than 0 and 1 or less (SJL 3), more than 1 and 2 or less (SJL 4), and more than 2 (SJL 5). The association between self-reported AP and other factors except for SJL was assessed by means of multinomial logistic regression analysis. Results: Factors significantly associated with good self-reported AP included female gender, lower grade, less sleepiness, lower BMI, intake of breakfast, less constipation, early wake-up time during the weekend, and short screen time during the weekend. The mean self-reported AP of SJL 3 was better than that of both SJL 5 and SJL 1. Conclusions: Self-reported AP was associated with gender, grade, BMI, sleep, breakfast, defecation, and screen time in children in grades 5 to 12 in Japan. It must be ensured that children take enough time to perform the indispensable human behaviors of sleeping, eating, defecation, and physical activity.